Enantioselective accumulation, elimination and metabolism of fenbuconazole in lizards (Eremias argus). (May 2021) - Hao, Weiyu; Zhang, Yanfeng; Xu, Peng; Xie, Yun; Li, Wei; Wang, Huili
Abstract: The enantioselective accumulation, elimination and metabolism of fenbuconazole in lizards were determined following a single-dose (25 mg/kg bw ) exposure to racemic or enantiomeric fenbuconazole. Accumulation of fenbuconazole was found in lizard fat with rac -form > enantiopure enantiomers. The enantiomer fractions (EFs) were higher than 0.5 in the blood, while EFs were less than 0.5 in the liver, brain, skin and stomach. There was conversion from (+)-fenbuconazole to (−)-fenbuconazole in lizard liver and conversion from (−)-fenbuconazole to (+)-fenbuconazole in lizard liver and blood. The results showed that enantioselective accumulation appeared in lizards, but the direction varied among blood and different tissues. The elimination half-lives ( t 1/2 ) of (+)-fenbuconazole were higher than those of (−)-fenbuconazole in the blood and liver, suggesting that (−)-fenbuconazole eliminated faster than (+)-fenbuconazole in these tissues. In addition, both (+)-fenbuconazole and (−)-fenbuconazole eliminated faster in the liver and stomach exposed to racemate than those exposed to enantiopure enantiomers. On the contrary, the form of racemate decreased the elimination rate of fenbuconazole in lizard fat. Synergistic elimination may occur when two enantiomers coexisted in lizard liver and stomach, while the racemate produced antagonistic elimination in lizard fat. Simultaneously, three metabolites, RH-6467, RH-9029&RH-9030 and keto-mchlorophenol, were discovered in lizard liver. Only two metabolites, RH-6467 and RH-9029&RH-9030, were found in lizard blood. RH-9029&RH-9030 were the major metabolites. The discovered enantiomers of (+)-fenbuconazole metabolites were different from those of (−)-fenbuconazole. The findings of this study may provide a better understanding of the enantioselective behaviors of chiral triazole fungicides in reptiles. Graphical abstract: Image 1 Highlights: Accumulation of fenbuconazole was found in lizard fat with racemate > enantiomers. Interconversion of fenbuconazole enantiomers appeared in lizard liver. (−)-fenbuconazole eliminated faster than (+)-fenbuconazole in the blood and liver. Fenbuconazole eliminated faster in the liver and stomach of racemate group. RH-9129&RH-9130 were the major metabolites in lizards.